Development of rhythmic movement activity teaching module based on project-based learning - Melaty Melaty; Eri Barlian; Khairudin Khairudin; Sri Gusti Handayani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to develop and evaluate a Project-Based Learning (PJBL) instructional module for rhythmic movement activities, specifically creative gymnastics, in senior high school physical education. Using the ADDIE development model, the research proceeded through analysis, design, development, implementation, and evaluation stages. Expert validation showed that the module achieved a very valid category, with the material expert scoring it at 88% and the PJBL expert at 90%, resulting in an overall validity of 89%. A small-group practicality trial demonstrated strong feasibility, with students rating the clarity, attractiveness, and usability of the module at an overall score of 88%, categorized as very practical. Effectiveness testing compared learning outcomes between two groups and revealed that the project-based class significantly outperformed the non-project class, achieving a mean score of 90% compared to 78%, yielding a 12% improvement attributed to the PJBL approach. These results confirm that the developed module is theoretically sound, practically feasible, and pedagogically effective. Overall, the module supports the goals of Kurikulum Merdeka by promoting creativity, collaboration, and student-centered learning in rhythmic movement activities.